XPC Promotes Pluripotency of Human Dental Pulp Cells through Regulation of Oct-4/Sox2/c-Myc - Lu Liu; Zhengjun Peng; Zhezhen Xu; Xi Wei (Stem Cells International)
Introduction. Xeroderma pigmentosum group C (XPC), essential component of multisubunit stem cell coactivator complex (SCC), functions as the critical factor modulating pluripotency and genome integrity through interaction with Oct-4/Sox2. However, its specific role in regulating pluripotency and multilineage differentiation of human dental pulp cells (DPCs) remains unknown. Methods. To elucidate the functional role XPC played in pluripotency and multilineage differentiation of DPCs, expressions of XPC in DPCs with long-term culture were examined by real-time PCR and western blot. DPCs were transfected with lentiviral-mediated human XPC gene; then transfection rate was investigated by real-time PCR and western blot. Cell cycle, apoptosis, proliferation, senescence, multilineage differentiation, and expression of Oct-4/Sox2/c-Myc in transfected DPCs were examined. Results. XPC, Oct-4, Sox2, and c-Myc were downregulated at P7 compared with P3 in DPCs with long-term culture. XPC genes were upregulated in DPCs at P2 after transfection and maintained high expression level at P3 and P7. Cell proliferation, PI value, and telomerase activity were enhanced, whereas apoptosis was suppressed in transfected DPCs. Oct-4/Sox2/c-Myc were significantly upregulated, and multilineage differentiation in DPCs with XPC overexpression was enhanced after transfection. Conclusions. XPC plays an essential role in the modulation of pluripotency and multilineage differentiation of DPCs through regulation of Oct-4/Sox2/c-Myc.